Terraforming Religious Consciousness: Race as a Signifier in New World Religious Cosmogony - Malik J. M. Walker (Religions, 2020)
What is the connection between race and religious diversity? This question has emerged as particularly important in recent times, following heightened discussions on racial justice, equity, and the organization of society with regard to racial oppression. The terms race and religious diversity imply distinct points of contact that have within them diverse perspectives and worldviews, that carry with them assumed foundational understandings of the world and unexamined understandings of how the universe functions. This article explores the connection between race and religious diversity by discussing the physical and intellectual landscape and by raising concerns about the historical and religious-symbolic background of the Atlantic World. This background assumes the fact that the Atlantic World is more than just a historical phenomenon. Instead, the formation and operation of the Atlantic World reveals the construction of a cosmogony that informs racial (social/relational) and religious discourse (imagination/intellectual). The Atlantic World cosmogony arose from the conquest of the Americas by European interests, resulting in a terraforming process that adapted the New World to European sensibilities. The story of the Atlantic World cosmogony and the terraforming of the Americas serve as two points of reflection that call for assessing the connection of race and religious diversity. Concomitantly, considering the foreground of the Atlantic World cosmogony and terraforming opens the possibility of resituating the way we critically approach the discourse on race and religious diversity, allowing for communities to candidly express efforts to move beyond the history of the effects generated by the conquest of the Americas.